Efetue:
![( - \frac{3}{5} )^{2} = ( - \frac{3}{5} )^{2} =](https://tex.z-dn.net/?f=%28+-++%5Cfrac%7B3%7D%7B5%7D+%29%5E%7B2%7D++%3D+)
![( + \frac{1}{2} )^{5} = ( + \frac{1}{2} )^{5} =](https://tex.z-dn.net/?f=%28+%2B++%5Cfrac%7B1%7D%7B2%7D+%29%5E%7B5%7D++%3D+)
![( + \frac{1}{3} )^{0} = ( + \frac{1}{3} )^{0} =](https://tex.z-dn.net/?f=%28+%2B++%5Cfrac%7B1%7D%7B3%7D+%29%5E%7B0%7D+%3D++)
Soluções para a tarefa
Respondido por
0
para o primeiro temo que saber que - com - é +
![( - \frac{3}{5} {)}^{2} = ( - \frac{3}{5} ) \times ( - \frac{3}{5} ) = \frac{9}{25} ( - \frac{3}{5} {)}^{2} = ( - \frac{3}{5} ) \times ( - \frac{3}{5} ) = \frac{9}{25}](https://tex.z-dn.net/?f=%28+-++%5Cfrac%7B3%7D%7B5%7D+%7B%29%7D%5E%7B2%7D++%3D+%28+-++%5Cfrac%7B3%7D%7B5%7D+%29+%5Ctimes+%28+-++%5Cfrac%7B3%7D%7B5%7D+%29+%3D++%5Cfrac%7B9%7D%7B25%7D+)
![( \frac{1}{2}) {}^{5} = \frac{1}{32} ( \frac{1}{2}) {}^{5} = \frac{1}{32}](https://tex.z-dn.net/?f=%28+%5Cfrac%7B1%7D%7B2%7D%29+%7B%7D%5E%7B5%7D++%3D++%5Cfrac%7B1%7D%7B32%7D+)
![( \frac{1}{3}) {}^{0} = 1 ( \frac{1}{3}) {}^{0} = 1](https://tex.z-dn.net/?f=%28+%5Cfrac%7B1%7D%7B3%7D%29++%7B%7D%5E%7B0%7D++%3D+1)
qualquer coisa elevada à 0 será igual a 1
qualquer coisa elevada à 0 será igual a 1
Perguntas interessantes
Inglês,
11 meses atrás
Matemática,
11 meses atrás
Saúde,
11 meses atrás
Biologia,
1 ano atrás
Ed. Física,
1 ano atrás
História,
1 ano atrás
Matemática,
1 ano atrás